STUDIO III 2018-2019 / Medicopark Maribor: študentski projekti študijskega programa Arhitektura prve stopnje (University of Maribor Press, 2019)
STUDIO III 2018-2019 / Medicopark Maribor: Students Projects of the Bachelor’s Study Program Architecture. The work in Studio III is based on the comprehensive integration of the broadest humanistic views, technical knowledge and skills with the art of architectural design, and on promoting awareness of the social responsibility of architects in the broadest social and cultural context. The peculiarity of Studio III’s work is the creation of thought through a model as the transfer of ideas into material ones. This winter’s semester it was necessary to create a conceptual design of the architecture for Medicopark Maribor, which was placed in a space along the Drava River in the extension of the UKC Maribor complex. Medicopark Maribor should, at the discretion of each student, comprise a wide variety of health services, dental and other outpatient clinics, diagnostic centers, beauty salons, wellness, fitness, alternative medicine facilities ... scattered throughout all possible and impossible locations in the city and they do not allow for their potential synergy. The tasks elaborated indicate an ambitious approach in the design of the baseline building volumetry and certainly showed interesting and varied possibilities for the development and exploitation of the area under consideration, while pointing out the dilemmas that open up.